Outcomes of Uretheral Strictures Treated with Endoscopic Urethrotomy and Urethroplasty - Noorshad Khan, Asif Khan, Mohammad Rashidullah, Sami Ur Rahman, Ghufranullah, Tausif Ahmad (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of this study is to determine the outcomes of uretheral strictures treated with endoscopic urethrotomy and urethroplasty. Study Design: Retrospective study Place and Duration: The study was conducted at Urology department of Saidu Group of Teaching Hospital, Swat for the duration of nine months from 1st January to 31st September 2021. Methods: There were sixty male patients underwent for uretheral strictures were presented in this study. After receiving informed written consent, demographic baseline parameters such as age, BMI, and comorbidities of enrolled cases were determined. Patents were divided into two groups, group I had 30 patients and received urethroplasty and group II received endoscopic urethrotomy. Complete follow up among patients of both groups were taken in duration of 4-6 months. Outcomes among both groups were assessed and compared in terms of post treatment success rate and complications. SPSS 22.0 was used to analyze all data. Results: In group I mean age of the patients was 50.8±13.61 years and had mean BMI 24.6±13.78 kg/m2 while in group II mean age was 52.5±11.91 years with mean BMI 25.7±9.87 kg/m2. Among all 60 cases, dysuria, urinary retention and pollakiuria were the symptoms. Most common cause was infectious found in 38 (63.3%) cases followed by urethral trauma in 14 (23.3%) cases. Membranous urethra was the most common site of urethral strictures. With a p-value of 0.04 after surgical treatment, a significant difference in Q max flowmetry was detected between the two procedures (urethroplasty 15.9±11.45 Vs 9.5 ±10.61 mL/s urethrotomy). Postoperative success rate was greater in group I 25 (83.3%) cases as compared to group II in 15 (50%) cases. Recurrence rate was higher in group II 8 (26.7%) cases as compared to group I 3 (10%). Conclusion: In this study, we found that urethroplasty is safer and more successful than endoscopic urethrotomy, with greater urine flow and a low recurrence rate.